Pelvic Inflammatory Disease: An Review and Homoeopathic Management (Homoeopathy for All, 2023)
Pelvic Inflammatory disease also is  an infection of upper part of female  reproductive system. This article  deals with an overview of Pelvic  Inflammatory disease, focusing  upon its various aspects along with  Homoeopathic management of the  same.
Keywords: Pelvic inflammatory disease; Homoeopathy